A novel crosslinker for synthesizing hypercrosslinked ionic polymers containing activating groups as efficient catalysts for the CO2 cycloaddition reaction. Issue 11 (18th May 2022) - Liao, Xu; Xiang, Xiaoyan; Wang, Zeyu; Ma, Ruixun; Kong, Lingzheng; Gao, Xilin; He, Jiao; Hou, Wenjuan; Peng, Cheng; Lin, Jinqing
Abstract : A novel crosslinker for synthesizing hypercrosslinked ionic polymers with high ionic content, high specific surface area and hydroxyl activating group as efficient heterogeneous catalysts for CO2 cycloaddition at atmospheric pressure. Abstract : It is crucial to explore highly efficient catalysts for the chemical conversion of carbon dioxide (CO2 ) into cyclic carbonates. Herein, a novel crosslinker 2-chloro-1, 1-dimethoxyethane was successfully used to prepare porous imidazolium-based hypercrosslinked ionic polymers (HIPs) with a large surface area (596 m 2 g −1 ), higher ionic content (0.971 mmol g −1 ) and an activating group (hydroxyl), which have a synergistic effect for CO2 capture (up to 3.22 mmol g −1, 273 K, 1 bar) and conversion. In the absence of co-catalysts, solvents, and additives, the catalyst HIP–Cl(3)–OH exhibited high yield and selectivity, and good substrate compatibility for the cycloaddition of CO2 with epoxides at atmospheric pressure in a short reaction time (3–6 h). High catalytic activities (styrene oxide, 120 °C, 8 h, 98% yield; 100 °C, 20 h, 98% yield) were achieved by appropriately extending the reaction time at low temperature, and the reaction time is shorter than that of most porous ionic catalysts previously reported under the same conditions. In addition, HIP–Cl(3)–OH showed excellent reusability and stability after six runs. The enhanced catalytic activity of the prepared HIP–Cl(3)–OH can be attributed to the use of a novel crosslinker and the in situ formed activating group embedded in the hypercrosslinked polymeric skeleton. This work highlights the coordination of high specific surface area, ionic content and activating groups, providing an effective metal-free heterogeneous catalyst for the CO2 cycloaddition reaction.